The Filipino struggle for intellectual freedom - Casillan-Garcia, Fe (1991)
This paper reviews the Filipino struggle for intellectual freedom from the Spanish occupation to the modern era. This struggle has always been an uphill battle due to psychological and socio-economic constraints. However, the Filipino spirit is undaunted-it tries to break loose from the fetters that bind it.
Keywords: Intellectual freedom